The new concepts in basic oncology research - Soeripto, Soeripto (Universitas Gadjah Mada, 1993)
Research on epidemiology, pathology, clinical course, and treatment of cancer is available. The epidemiological and clinical research on cancer must be brought into a comprehensive scheme. Basic research on oncology is suggested to be based on cancer epidemiology, and applicable for clinical practice. This article discusses the new concept of basic oncology research using breast cancer as a model.It is concluded that the new concepts in basic oncology research have to be based on the community need. It will be better if the research is multidisciplinary and multiinstitutional approach. Using this approach the expectation is that and the result could solve the problem either in the community or in the hospital.Key Words: oncology-cancer epidemiology-breast cancer oncogen-immunohistoclinical signs -prognostic index